Dinâmica populacional de Micrepeira hoeferi Levi 1995 (Araneae, Araneidae) - Morales, Juan Camilo Franco (2023)
Populations are dynamic systems that fluctuate in size over time, due to reproductivephenomena, which are also influenced by exogenous variables. The reproductive processes ofeach species are part of the life history, which correspond to the different ways in which thespecies achieve reproductive success, by which they guarantee the presence of the species overtime, thus avoiding extinction. The spider Micrepeira hoeferi Levi, 1995 (Araneae, Araneidae)belongs to a family of orb-weaver spiders, within which the genus Micrepeira has only beendescribed, knowing very little about its species. The present study aims to (i) report the speciesfor the first time in the state of Ceará, in northeastern Brazil, contributing data to the Wallaceanshortfall of the species, and (ii) describe the population variation of Micrepeira hoeferi, as wellas the influences of abiotic conditions on population fluctuation, providing data for thePrestonian shortfall and the Hutchinsonian shortfall. The first chapter reports the first record ofMicrepeira hoeferi, in the Área de Proteção Ambiental da Serra do Baturité, in Pacoti, Ceará;in addition to reporting the species, it expands its tolerance range to higher areas and therainforest, as well as proposing a morphological variation for the species. The second chapterdescribes the population fluctuation and phenology of Micrepeira hoeferi. Over a year, themonthly abundance was recorded in a 200-meter transect located in Pacoti, Ceará. There were361 individuals distributed in 5 instars. The spiderling instar represented most of theindividuals. All instars had significant differences in monthly abundance, with marked peaks.Males only occurred during the rainy season, thus denoting the reproductive season of thespecies, which is why we cataloged Micrepeira hoeferi as a stenochronous rainy season species,a fact confirmed by the discovery of 4 ootheca in the same period. Precipitation and temperaturevariables did not have a significant influence on the monthly abundance of the species.